The Role of Islamic Religious Education Teachers in Cultivating Positive School Culture: A Multisite Case Study at SMPN 6 Torgamba - Marlina Marlina; Zailani Zailani; Nur Rahmah Amini (MASI Mandiri Edukasi, 2025)
Creating a positive school culture is essential for fostering students' moral, social, and academic development. In this context, Islamic Religious Education (PAI) teachers are seen as key agents in cultivating value-based environments within educational institutions. This study aims to analyse the role of PAI teachers in shaping a positive culture at SMPN 6 Torgamba by identifying the forms of positive culture developed, the teachers’ planning strategies, their functional roles, and the supporting and inhibiting factors involved. A qualitative method with a case study approach was applied, utilising participatory observation, in-depth interviews, and a documentation study. The findings reveal that five core aspects of positive culture have been developed at the school: religious culture, discipline culture, literacy culture, mutual cooperation culture, and tolerance culture. PAI teachers’ planning encompasses learning, religious programs, collaboration, and self-development. Their roles are embodied in six dimensions: as educators (mu’allim), role models (uswatun hasanah), mentors (mursyid), motivators, cultural facilitators, and evaluators. Key factors include school policy support, inter-teacher collaboration, active student engagement, parental and community involvement, and adequate facilities. Conversely, challenges include time constraints, diverse student backgrounds, negative technological influences, limited teacher competencies, and resistance to change. This study highlights the strategic role of PAI teachers in driving cultural transformation and recommends greater institutional support for character-based education in public schools.